Syntheses, crystal structures, and magnetic properties of four novel Cu(I/II) complexes - Zhu, Xiaofei (2013)
Four coordination compounds CuIICuI(O2N-ipO)(4,4′-bpy) (1), [CuII6(O2N-ipO)4btp(H2O)8]·6H2O (2), [CuII12(O2N-ipO)8(bth)4(H2O)10]·2H2O (3), and [CuII18(O2N-ipO)12(btp)3(H2O)18(EtOH)6]·13H2O (4) (4,4′-bpy = 4,4′-dipyridyl, btp = 1,3-bis(1,2,4-triazol-1-yl)propane, bth = 1,6-bis(1,2,4-triazol-1-yl)hexane and O2N-ipO = deprotonated 5-NO2-2-hydroxyisophthalic acid, Chart 1) were synthesized and crystallographically characterized. The common building unit [Cu2(O2N-ipO)2] (O2N-ipO = deprotonated 5-NO2-2-hydroxyisophthalate, in-situ formed in the reaction of 5-NO2-1,2,3-benzenetricarboxylic acid (O2N-btcH3) with CuCl2·2H2O under hydrothermal conditions) features a diamond-shaped dinuclear motif, in which two Cu atoms are bridged by the deprotonated 2-hydroxo groups from different O2N-ipO ligands. Compound 1 exhibits a three-dimensional (3D) wave-like structure composed of [CuII2(O2N-ipO)2]2− and [CuI2(4,4′-bpy)2]2+ subunits, while 2 displaying a 1D alternate double-chain structure based on units of [CuII2(O2N-ipO)2] and [CuIINO4]. Compounds 3 and 4 are discrete polynuclear species featuring a dodeca- and a octadeca-nuclear core based on units of [CuII2(O2N-ipO)2] and [CuIINOn], respectively. These compounds were further characterized by elemental analyses, FTIR, PXRD and thermogravimetric analyses. In addition, we studied their magnetic properties via direct current magnetic susceptibility measurements.